ANALISA KEMITRAAN PERBANKAN PADA PELAKU USAHA MIKRO DI ERA DIGITAL - Wening Purbatin Palupi Soenjoto (Faculty of Islamic Economic and Business (FEBI), Sayyid Ali Rahmatullah State Islamic University (UIN SATU) Tulungagung, 2022)
Banking in the current digital era has various impacts, from facilitating the use of demand deposits to financial transactions that require digital skills in the use of banking products. Not all customers have digital skills in banking product transactions and this is an obstacle that must be a concern for bankers. The banking sector is even now starting to approach business actors in terms of financing that can be done by business actors while continuing to carry out the procedures and policies carried out by each bank. micro and small business actors. Micro business actors still use a lot of currency in transactions and even to enter into partnerships with banks is still constrained by the conditions imposed by the bank. Business actors in Indonesia are classified into UMKM’s, namely Micro, Small and MSMEs. enengah.In Indonesia, in fact, there are more micro business actors than medium and large businesses that are more involved in partnerships with banks. There are still many micro business actors who have not entered into partnerships and transactions are still simple and the use of digital technology in production is still minimal. , transactions and marketing. The implementation of banking partnerships is still constrained by several policies implemented by banks and the government so that there has not been an optimal partnership that has occurred in business actors in Indonesia. primary and secondary library sources to analyze and examine banking partnerships in entrepreneurship in the digital era.